Peran Madrasah dalam Membentuk Karakter Siswa Kelas IV untuk Menghadapi Era Digital Di MI Al Mu’awanah Cibinong Bogor - Hadiyanti Dini Islamiati, Siti; Suryana, Agus; Juneidi; Kurniasih, Euis; Maulida Muslina, R. Maya; Maryati, Yati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Madrasahs as educational institutions play a very important role in the character building of students. Madrasahs are responsible for the moral education of students and more so than other educational institutions. Madrasah is a place to provide moral and moral education, not just a place to learn science. The purpose of the research conducted was to reveal the Role of Madrasahs in Shaping the Character of Grade IV Students to Face the Digital Age at MI Al Mu'awanah Cibinong Bogor. The method used in this research is qualitative research and data collection is done by means of observation, interviews, documentation While data collection is done by collecting primary and secondary data in the field. The results showed that 1) Madrasah already has a vision to create a generation that is intellectually intelligent, and also noble and adaptive to technological developments and a mission to improve the ability to use information and communication technology (ICT) to support the learning process of teachers and students in schools. 2) Madrasah shape students' character by teaching digital literacy to students so that they can navigate the digital world intelligently and critically, and avoid negative content 3) Madrasah shape students' character by explaining to students about the negative impact of gadget addiction and directing students to make a schedule for gadget use and interesting alternative activities such as sports, arts, or traditional games and extracurricular programs.